Use of Lead Isotopic Ratios as Geographical Tracer for Lambrusco PDO Wines - Lisa Lancellotti; Simona Sighinolfi; Andrea Marchetti; Lorenzo Tassi (Molecules, 2020)
In this study, the lead isotope signature was tested with the aim to verify its potential as geographic tracer for wine production and particularly for the Lambrusco PDO wines of the province of Modena (Italy). A solid phase extraction procedure, for separating lead from the investigated matrices, soil and wine, was optimized. Furthermore, different mathematical models, based on an exponential law and internal or external correction approach, were evaluated for the correction of instrumental mass dependent fractionation. The optimized analytical procedure yielded isotopic ratio data relative to the lead NIST 981 standard, 208Pb/206Pb = 2.16664 and 207Pb/206Pb = 0.914645, in good agreement both with the tabulated values and with the most recent literature data. Measured isotope ratio data highlight the contribute of multiple lead sources in bottled wine but different from the one present in soils.